PENGEMBANGAN SISTEM INFORMASI PENGELOLAAN LAPORAN KEUANGAN DANA PENSIUN Studi Kasus : DANA PENSIUN PEMBINA POTENSI PEMBANGUNAN - Paramitha Dahlan; Muhammad Sholeh; Naniek Widyastuti (Jurusan Informatika INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA, 2016)
Dana Pensiun Pembina Potensi Pembangunan has operating since 2006 and improved in 2008. Administration in Dana Pensiun Pembina Potensi Pembangunan is among others on the financial statements still work manually, the administrator should write all of transactions on a book, then the data is inserted into ms.excel, then that data will be managed as financial reports. Therefore, in the data processing required a system that could make it easier to produce financial reports.The sytem is built using PHP, HTML, CSS, and Javascript as programming language. Mysql as database management system, apache as web server and system design using UML. The workings of this system that administrators have to input all the data required financial reports into the system, then the system will process them and generate financial reports. The output from this system can be printed. The existence of these financial reports management system can ease the burden on the Dana Pensiun Pembina Potensi Pembangunan to manage income and expenditure transaction data, investment data, and asset data. In addition to process data, the system can also store all the recaps data that can be accessed again at a later time. The system can also provide financial reports that provide information development of pension funds, so as to facilitate the management in presenting the report the required leadership.